Интеллектуальные средства диагностики компьютерных систем - Кривуля, Г. Ф.; Давыдов, А. А. (ХНУРЭ, 2008)
Result of performance of such task was: formation of knowledge’s base of malfunctions in modern personal computers, formation of the list of malfunctions, an establishment of the reasons of their occurrence and development of the application of on search and elimination. In this work stages of transition from general principles of intellectual diagnostics to realization of the put task, by creation of the application on search of malfunctions.
Keywords: диагностика компьютерных систем